Response variability in Attention Deficit Hyperactivity Disorder: evidence for neuropsychological heterogeneity - BELLGROVE, MARK; GILL, MICHAEL; JOHNSON, KATHERINE ANNE; ROBERTSON, IAN (My University, 2007)
Response time (RT) variability is a common finding in ADHD research. RT variability may reflect frontal cortex function and may be related to deficits in sustained attention. The existence of a sustained attention deficit in ADHD has been debated, largely because of inconsistent evidence of time-on-task effects. A fixed-sequence Sustained Attention to Response task (SART) was given to 29 control, 39 unimpaired and 24 impaired ADHD children (impairment defined by the number of commission errors). The response time data was analysed using the Fast Fourier Transform, to define the fast-frequency and slow-frequency contributions to overall response variability. The impaired ADHD group progressively slowed in RT over the course of the 5.5 minute task, as reflected in this group?s greater slow-frequency variability. The fast-frequency trial-to-trial variability was also significantly greater, but did not differentially worsen over the course of the task. The higher error rates of the impaired-ADHD group did not become differentially greater over the length of the task. The progressive slowing in mean RT over the course of the task may relate to a deficit in arousal in the impaired-ADHD group. The consistently poor performance in fast-frequency variability and error rates may be due to difficulties in sustained attention that fluctuate on a trial-to-trial basis.
PUBLISHED
Keywords: Sustained attention; response time; fast Fourier transform; frontal cortex; endophenotype